Antibiotic Treatment based on Guidelines for Reducing Length of Stay (LOS) in Patients with Community Acquired Pneumonia (CAP) - Munarsih, Fetri Charya; Natadidjadja, Ronald Irwanto; Syamsudin, Syamsudin (Jurnal Penyakit Dalam Indonesia, 2018)
Introduction. Community acquired pneumonia (CAP) now is known as the most common infection presented. Empiric antibiotic administered followed by observing parameters. This study aimed to know how far the American Thoracic Society/ Infectious Disease Society of America (ATS/IDSA) antibiotic guidelines 2007 based treatment influenced the length of stay (LOS) of CAP subject in a private hospital ward between January 2014-August 2015 Methods. A retrospective cohort was conducted with bivariate analysis and multivariate analysis for reducing the confounding factor. Sample taken with proportional sampling formula at ward in a hospital in Jakarta. Results. The result showed that subjects with unproper empiric antibiotic based on ATS/IDSA 2007 guidelines tent to have hospital prolong stay 10.25 times (p <0.001) than others with proper on ATS/IDSA empiric antibiotic guidelines. Conclusion. By this result, we observed a very significant statistic result difference in LOS between a group with proper empiric antibiotic based on ATS/IDSA 2007 guidelines and other who unproper.